Regional Development Strategies in New Growth Center Around Barsela Special Economic Zone (SEZ), Southwest Aceh Regency - Husna, Cut Zulfa; Pravitasari, Andrea Emma; Putra, Andi Syah (The Indonesian Journal of Planning and Development, 2025)
Aceh Province has significant regional disparities, especially in the Southwest (Barsela). However, this region is strategically located, prompting the government to develop a strategic area that is the Barsela Special Economic Zone (SEZ) in Southwest Aceh Regency, which is located in Babahrot District, with Kuala Batee District as the closest hinterland. These two districts have the highest poverty rates in the regency, making the SEZ a potential catalyst for new growth center. This study aims to determine priority villages as new growth centers and regional development strategies using scalogram, gravity, network analysis, AHP-TOPSIS, and SWOT methods. Scalogram analysis shows that most villages around the Barsela SEZ have low regional development, with 54% in Hierarchy III, 29% in Hierarchy II, and 17% in Hierarchy I. Gravity analysis indicates low to moderate regional interactions, with NTIAD below 4,000,000 interaction units. Road network centrality is also generally low, with only four villages classified as high, based on Degree Centrality (0.31), Closeness Centrality (0.26), and Betweenness Centrality (0.43). Based on AHP-TOPSIS, Pante Rakyat Village is prioritized as a new growth center due to its high regional development, strong attractiveness, and good spatial centrality. The main development strategy is the Turnaround Strategy, which focuses on utilizing opportunities and addressing weaknesses. This research is expected to support spatial planning around the Barsela SEZ and contribute to Southwest Aceh Regency and Aceh Province government policies.